2006
DOI: 10.1016/j.amjcard.2005.07.109
|View full text |Cite
|
Sign up to set email alerts
|

ST-Segment Analysis to Predict Infarct Size and Functional Outcome in Acute Myocardial Infarction Treated With Primary Coronary Intervention and Adjunctive Abciximab Therapy

Abstract: ST-segment resolution is used to classify the response to reperfusion therapy in acute myocardial infarction, but the possibility to predict outcome in individual patients is unclear, particularly in the setting of primary percutaneous coronary intervention (PCI) and abciximab therapy. We studied 213 patients who underwent successful revascularization with PCI. Maximal ST-segment elevation was measured before and 30 minutes after PCI. Patient outcome was defined on the basis of infarct size and left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Similarly, Poli et al (15) showed no additional predictive value of ST-segment resolution when summed to MBG with respect to 6-month functional recovery. Finally, Sciagrà et al (17) found, in the setting of patients who were treated with primary stenting and abciximab, a relatively low correlation between ST-segment resolution and infarct size and EF, suggesting the use of ECG findings only to categorize outcome as favorable or unfavorable but not to assess infarct size or LV function. In this multicenter study, we confirm and highlight the weak correlation between ST-segment resolution and EF and WMSI at 6-month follow-up, and we demonstrate that this ECG parameter is not able to predict post-infarct LV remodeling.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Poli et al (15) showed no additional predictive value of ST-segment resolution when summed to MBG with respect to 6-month functional recovery. Finally, Sciagrà et al (17) found, in the setting of patients who were treated with primary stenting and abciximab, a relatively low correlation between ST-segment resolution and infarct size and EF, suggesting the use of ECG findings only to categorize outcome as favorable or unfavorable but not to assess infarct size or LV function. In this multicenter study, we confirm and highlight the weak correlation between ST-segment resolution and EF and WMSI at 6-month follow-up, and we demonstrate that this ECG parameter is not able to predict post-infarct LV remodeling.…”
Section: Discussionmentioning
confidence: 96%
“…However, even though primary angioplasty has been shown to provide larger benefits as compared with thrombolysis, a suboptimal myocardial reperfusion is observed in a still relevant proportion of patients, despite optimal epicardial recanalization [7][8][9]. Hypertension is an established risk factor for atherosclerosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…To identify the independent association of ST peak with infarct size and LVEF, multivariable regression analyses were performed using ST peak and known predictors of infarct size and LVEF such as anterior infarct location, symptoms-to-balloon time, preprocedural TIMI flow, baseline ST elevation (in millimeters), and ST resolution (30, 60, and 90 minutes after reperfusion). 32,33 Because of expected colinearity between ST resolutions after 30, 60, and 90 minutes, respectively, only the best of the 3 in the univariable analyses was used in the multivariable approach. The potentially confounding effect of exenatide and IPost was evaluated by interaction between ST peak and exenatide/IPost treatment and by adjusting for exenatide/IPost vs conventional treatment in a linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%